An economic model of asset division in the dissolution of marrage - Fethke, Carol C. (American Economic Review, 1984)
Recent statistics indicate that more than one-third of all new marriages will end in divorce. This evidence suggests that even the most happily couples may be wise to view their lifetime choices within a framework that recognizes that periodically each selects one of two strategies: married or not married. When both select the married strategy, the couple remain married. If either party (or both) elect the not-married strategy, the outcome will be divorce. Election of the not-married strategy thus creates a twoperiod world in which each party is married in the first period and divorced in the second. When a marriage dissolves, the couple divides all marital property either by mutual consent or according to the division rules imposed upon them by the state in which they reside. The law separately defines both marital property and the formula used to divide the property. This paper focuses on the interaction of the two variables, specifically, the effect of the state's division rule on the savings-consumption decisions of a divorcing couple.' Savings are of interest because they represent the couple's marital assets; the division rule is important because the amount each party receives at divorce affects the postmarriage economic well-being of each. The analysis can improve our understanding of the economic behavior of couples and will provide insight into the effect of divorce law on family savings patterns. Since law views divorcing spouses as adversaries, the analysis of marital savings and the resulting property division is carried out in a noncooperative game framework in which couples facing divorce each protect their self-interest by maximizing separate lifetime utility functions.2 Three noncooperative games are discussed: Cournot, Stackelberg, and Nash bargaining.